Notes on a Silver-mounted Charm-Stone of Rock-Crystal from Inverleny, with Notices of other Scottish Balls of Rock-Crystal and of Superstitions connected therewith - Black, George F (Proceedings of the Society of Antiquaries of Scotland, 1895)